The Influence of Student Personality on Akhlak Establishment in SMK Gelora Pancasila Pengajahan - Candra Wijaya; Budi Suhartono; Hamzah Hamzah; Awaluddin Awaluddin (Budapest International Research and Critics University, 2020)
This study aims to describe the effect of student personality on moral formation at SMK Gelora Pancasila Pengajahan with a quantitative descriptive approach. This study took a sample of SMK Gelora Pancasila Pengajahan Medan City. Of the 22 samples that the author distributed from SMK Gelora Pancasila Pengajahan were analyzed using Moment Products to see the effect. The hypothesis is that there is a significant influence on Student Personality Formation on Moral Formation in Gelora Pancasila Pengajahan Vocational Schools. Research locations at SMK Gelora Pancasila Pengajahan Medan City class IX. The results showed that there was a significant effect of student personality on the formation of student morals with the correlation coefficient amounted to 0.429, or 18.44%.